دور التدريب في تفعيل إستراتيجية تنمية الموارد البشرية عبدالله سليمان عبدالله الكابوري النقي - Abdulla Suliman Abdulla Alkabouri Alnaqbi; Ibrahim Fahad Sulaiman (worldconferences.net, 2024)
Non-Indexed Publication